Chronic high glucose and insulin stimulate bone-marrow stromal cells adipogenic differentiation in young spontaneously hypertensive rats - Chaves Neto, Antonio H. [UNESP]; Brito, Victor G. B. [UNESP]; Landim de Barros, Thamine [UNESP]; do Amaral, Caril C. F. [UNESP]; Sumida, Dóris H. [UNESP]; Oliveira, Sandra H. P. [UNESP] (Wiley, 2018)
We evaluated whether genetic predisposition is sufficient to induce changes due to chronic high glucose (HG; 25 mmol/L) in the presence or absence of insulin (HGI; 10 μg/ml) on osteogenic differentiation and markers in bone-marrow mesenchymal stem cells (BMSCs) from young Wistar (WBMSCs) and spontaneous hypertensive rats (SBMSCs) without hypertension. HG suppressed osteogenic differentiation in both the strains, observed by mineralization inhibition and decreased levels of the osteogenic markers Runx2, osterix, osteopontin, and bone sialoprotein, compared to osteogenic medium (OM) cells. In WBMSCs, the effects of HG were associated with the down regulation of ERK1/2 and up regulation of p38 activities; however, HGI did not revert the effects of HG on MAPK activities. Moreover, HG did not affect MAPK signaling in SBMSCs compared to that in OM. HGI increased mineralization in WBMSCs compared to that in OM, but not in SBMSCs. High expression of peroxisome proliferator-activated receptor-gamma and glucose transporter type 4 in OM could be related with the predisposition to adipogenic differentiation noted in SBMSCs and was confirmed by emergence of adipocyte-like cells by HGI treatment. Downregulation of p38 and upregulation of JNK activities were observed in both BMSCs treated with HGI compared to those treated by HG. Ma (osmotic control) also suppressed osteogenic differentiation in both the strains. In conclusion, we demonstrated that SBMSCs from young spontaneous hypertensive rats, without hypertension but with genetic and epigenetic predisposition, exhibited decreased osteoblastic differentiation under HG and HGI did not revert the effects of HG in SBMSCs but increased adipogenic differentiation.
Keywords: glucose; hypertensive phenotype; insulin; mannitol; osteoblast